The Call to Holiness according to Gaudete et Exsultate and its Relevance in the Juniorate Formation of Beoto Mario Borzaga OMI Indonesia - Hendrianus Wendi (Jurnal Pelayanan Pastoral, 2026)
The era of globalisation is characterised by rapid social, cultural, economic, and digital transformations that significantly influence the faith life of believers. These changes often promote individualistic, consumerist, and pragmatic lifestyles that risk distancing people from the Christian call to holiness. In response, Gaudete et Exsultate, issued by Pope Francis, reaffirms the universal call to holiness as concrete, accessible, and rooted in daily life. Holiness is not an elitist ideal reserved for a few, but a way of living grounded in God’s grace and expressed through fidelity in ordinary responsibilities. This study examines and synthesises the concept of holiness in Gaudete et Exsultate with the spirituality of Blessed Mario Borzaga, highlighting its relevance for the formation of OMI Juniors. The research uses a pastoral theology approach with a qualitative method through literature review. The findings show that, according to Pope Francis, holiness is embodied in five key elements: embracing one’s authentic identity, sanctifying daily life, avoiding Gnosticism and Pelagianism, persevering in goodness, and living the Beatitudes. These dimensions are clearly reflected in the life of Blessed Mario Borzaga as priest, missionary, and martyr. The synthesis offers a reflective and practical framework for OMI Junior formation, ensuring that holiness becomes not merely a normative ideal but a lived, contextual response to the challenges of globalisation